Asylum on the Hill : History of a Healing Landscape. - Ziff, Katherine; Gladding, Samuel T.; Shields, Joseph; Bolin, Shawna (Athens, OH : Ohio University Press, 2012)
Asylum on the Hill is the story of a great American experiment in psychiatry, a revolution in care for those with mental illness, as seen through the example of the Athens Lunatic Asylum. Katherine Ziff's compelling presentation incorporates rare photos, letters, and records, offering readers a fascinating glimpse into psychiatric history.
Praise for Asylum on the Hill -- Title Page -- Copyright -- Contents -- Foreword -- Preface -- Acknowledgments -- 1. The Moral Treatment Experiment: "A Magnificent Site Overlooking the Hocking Valley" -- 2. Patients: "Each Admission Represented a Poor, Helpless, Hopeless Sufferer" -- 3. Architecture: "Space, Light and Air to Each Patient" -- 4. Politics: "Partisan Interests and Personal Place-Seeking" -- 5. Landscape: "Of Beautiful and Varied Scenery" -- 6. Caregivers: "To Take Proper Care of the Insane Requires Talents of a High Order" -- Epilogue -- Afterword: to the 150th Anniversary Edition -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Athens State Hospital--History.; State hospitals--Ohio--Athens--History.; Psychiatric hospitals--Ohio--Athens--History.; Psychiatric hospital care--History.; Mental illness--Treatment--History.; Electronic books